O mercado, os homens e alguns segredos: uso da metodologia multimétodo para identificação do conceito de fato relevante no crime de insider trading - Santos, Ives Nahama Gomes dos (2023)
The research deals with the characterization of fact, in a crime of Brazilian criminal investigation, in the years of Brazilian criminal investigation, in the years 2001-20, for receiving a complaint20, disclosure by classification and analysis. It starts from the theoretical framework of the capital market, the role of information and as delimitations on the use of privileged information to learn how to use the concept of the capital market, as well as its translation as a penal norm to meet the principles of the market. It discusses how the principle of transparency was established by the Corporate Laws in Normative Instruction 358/02 and Resolution 4/21 of the Securities and Exchange Commission and its repercussions on the Brazilian legal system. From the study of administrative decisions applying the Decision Analysis Methodology – MAD. It adopts a multi-method methodology, of document analysis and survey of approved and qualitative data from nine criminal cases dealing with the use of privileged information, answering the Content Analysis questions: 1) Who speaks? 2) To say what? 3) Who? 4) In what way? 5) For what purpose? 6) With what results they will verify the established facts to determine the concrete case. It faces as public availability of the presence of a database and confidence of the number of shares of internal trading actions, as well as the very presence in the Federal Criminal Courts. Conclude that the cases must be concluded to define the determination of facts, 6 established in the definition, and 1 the software presented in the disclosure, and the result of classification by the Reinert method, resulted from the classification by the Reinert method, result of the analysis by the method of Reinert, which resulted from the analysis by Reinert's method, of the existence of an analysis of blocks of criteria for definition of relevant fact by the Criminal Judiciary, responding positively to the research problem. It is concluded that the case1 of the research is still being the case of conclusion of more of the fact that is being considered in five foundation blocks. by the protection mechanisms of protection mechanisms as urgent protective measures in the context of the femicides studied. After checking the hypotheses, only one confirmed restoration. In the end, there are ideas of models defined in behavioral studies, such as what are the problems defined and elements in the performance of the Judiciary, namely: simplification, tendency and preparation.